Potential value of arbuscular mycorrhiza in the agricultural systems of Alentejo region - Portugal - Brito, Isabel Maria de Oliveira (2008)
The Alentejo region, located in the south of Portugal and occupying a third of the continental part of the country, is the region with the greatest potential for small grain production. It produces more than 80% of the total national wheat harvest, the main small grain cereal crop, despite small average yields per unit land area. The restrictions to yield are largely imposed by its Mediterranean climate, with dry and hot summers and cold and wet winters. Soil limitations can also constrain yield. Development of biomass up to the flowering stage is critical for achieving good grain yields in wheat. Consequently, agronomic management practices, including appropriately designed crop rotations, focused on achieving good early crop development, together with low input systems based on no-till, and a rational use of nutrients, can contribute, to increased productivity in the region. A possible mean of improving the use of nutrient resources is through the improved management of naturally occurring symbioses like arbuscular mycorrhiza. Arbuscular mycorrhiza (AM), a symbiosis between the roots of a wide range of plants and obligatory symbiotic fungi, is commonly mutualistic, the long-term compatible interactions being based on a bidirectional nutrient transfer between symbionts. Fungal symbionts benefit from the photosynthates produced by the plants, while the latter gain because of the increased volume of soil that can be explored by the extraradical fungal mycelium. This enhanced soil exploration is one of the most obvious advantages of mycorrhizal formation and results in the ability to take up more nutrients, particularly those that have limited mobility in soil, such as phosphorus. In addition other benefits associated with AM plants are: alleviation of water stress, protection from root pathogens, tolerance to toxic metals and the stabilization of soil aggregates promoted by extraradical hyphae, globally conferring to AM a great potential to contribute to sustainable crop production systems. Considering the impracticality of inoculating soil on a large scale, the objectives were focused on the potential value of AM under Mediterranean conditions and how they could be managed within the agricultural system of Alentejo region, assuming that if there is adequate AM colonisation, benefits would directly or indirectly, sooner or later, accrue to the crop. In a field experiment preformed to study the effect of soil disturbance (notill and conventional tillage systems) on AM colonisation of wheat over the vegetation cycle the results indicated that mycorrhizal formation in wheat and AM fugal spore numbers were greater in no-till than under a conventional system, despite the high level of soil available phosphorus. Results also showed that under field conditions, AM colonisation of winter wheat increased gradually until late spring and then declined, following root development. Once AM colonisation of wheat under Mediterranean conditions was confirmed at the field and that there was better colonisation under no-till systems, where the extraradical mycelium was kept intact, the next objective was to determine the ability of this mycelium to remain infective for the next crop. The maintenance of a high colonisation potential under the Mediterranean summer conditions is essential because it likely determines the time frame (from one cropping year to the other) and the possibilities (faster or slower colonisation) for AM to influence early crop development. Extraradical mycelium of native AM fungi (AMF) survived the dry and hot summer season and started new colonisations at the onset of the growing season, especially when it was not adversely affected by soil disturbance. The proper management of weed populations that emerge after the first autumn rains might provide a valuable too), functioning as a bridge, to ensure a quick and efficient AM colonisation of wheat young seedlings and help to assure a good early development known to be critical for successful wheat crop in Alentejo region. In a series of pot experiments using weed species chosen according to their relevance in regional agronomy, it was confirmed that allowing weeds to growth until extraradical mycelium is well established (one month) and then using herbicide to control them, preserves the extraradical mycelium network and greatly benefits initial colonisation of the crop and permits early nutrient acquisition. Considering there are pronounced plant x fungus interactions, a more diverse AM fungal community offers more possibilities for functional AM symbioses to establish. ### /RESUMO - A região do Alentejo situa-se no Sul de Portugal e corresponde a cerca de um terço do território continental. Por uma série de razões como sejam a situação geográfica o relevo e a dimensão da propriedade, é a região do país que apresenta maior potencial para a produção cerealífera, contribuindo com cerca de 80% da produção nacional de trigo, até ao momento o principal cereal produzido em Portugal. No entanto, devido em grande medida a limitações edafoclimáticas, as produtividades obtidas são relativamente baixas quando comparadas com outros países europeus. O clima Mediterrânico, caracterizado por Verões quentes e secos e Invernos frios e chuvosos, obriga à utilização de variedades de ciclo relativamente curtos, para além disso a distribuição de precipitação é extremamente irregular provocando grandes oscilações de produção de ano para ano. Nestas condições, e para os cereais de Inverno no geral, a biorriassa, acumulada até à floração é determinante para a garantia de um bom enchimento do grão, por isso o crescimento inicial da cultura pode ser decisivo para alcançar uma boa produtividade. Os solos são na sua maioria relativamente pobres. Derivados de xistos ou granitos, apresentando baixos teores de matéria orgânica, pH ligeiramente ácido e média capacidade de troca catiónica. A adesão de Portugal à Comunidade Europeia em 1986, e a obrigatoriedade em seguir as directivas da Política Agrícola Comum (PAC) cada vez mais baseadas na redução de subvenções aos agricultores, exigiu o repensar do sistema agrícola da região. A procura de sistemas de produção mais sustentáveis do ponto de vista ambiental e financeiro tornou-se obrigatória para a sobrevivência do sector agrícola. Assim, a aplicação de fundos estruturais no desenvolvimento e aquisição de novos meios de produção, o recurso a sistemas mais extensivos, o aumento da mecanização e o uso mais racional de factores de produção, têm vindo a operar uma mudança significativa no sistema agrícola do Alentejo. Exemplo disso mesmo é o recurso cada vez mais generalizado à técnica de sementeira directa, actualmente praticada em várias culturas (trigo, milho, girassol) em mais de 50 000 ha. Sistemas de baixo input baseados na sementeira directa, associados a um correcto delineamento da rotação de culturas e ao uso racional dos nutrientes são, em termos práticos, potenciais geradores de aumentos da produtividade. Neste contexto o recurso a simbioses que ocorrem de forma natural, como as micorrizas arbusculares, pode constituir uma importante via para a exploração mais adequada dos nutrientes do solo. As micorrizas arbusculares (AM) são simbioses entre a raiz de uma grande diversidade de plantas e fungos do solo que são simbiontes obrigatórios, os fungos micorrízicos arbusculares (AMF). Esta associação simbiótica é normalmente mutualista, baseando-se na troca bidireccional de nutrientes. O fungo recebe da planta os produtos resultantes da actividade fotossintética e a planta, por sua vez, beneficia de uma série de vantagens decorrentes da exploração de um maior volume de solo proporcionado pelo micélio extraradical que se desenvolve, sendo a absorção de nutrientes, nomeadamente os menos móveis como é o caso do fósforo, a mais óbvia. Contudo, para além desta, outras vantagens são atribuídas às AM: alívio do stress hídrico, protecção contra agentes patogénicos, tolerância a metais pesados e estabilização dos agregados do solo, mostrando assim um enorme potencial no contributo para a produção agrícola sustentada. Pretendeu-se com o presente trabalho compreender o potencial associado às AM, em situação de clima Mediterrânico, no contexto do sistema agrícola Alentejano, no sentido de através de práticas agrícolas adequadas valorizar os benefícios proporcionados pela micorrização, numa óptica de sustentabi 1 idade do sistema agrícola. Assumiu-se que uma vez estabelecida a micorrização, os benefícios daí decorrentes, directa ou indirectamente, mais cedo ou mais tarde, recairiam sobre a cultura. Assim, no sentido de desenvolver conhecimentos que elucidassem sobre a ecologia funcional das micorrizas arbusculares no sistema agrícola em apreço, adoptou-se uma abordagem multidisciplinar de modo a que a integração e análise da informação a diferentes escalas pudesse ser feita.